PENGARUH PROSES IN-SERVICE WELDING PADA NILAI KEKERASAN SAMBUNGAN [Influence Of In – Service Welding Process On Joining Metal Hardness Value ] - Martides, Erie (Jurnal Metalurgi, 2015)
Welding is a reliabel method to joints two material or more, and its use in instalation process, maintenance and repairing process. In-services welding is joining the pipe material, where the pipe in working condition which still flowed by fluids. Joining process conduct between 2 API 5L X60 pipes using fillet joints type, SMAW process and 5F position. Specimen of welded materials tested and inspected in laboratory, the tests encompass bending, hardness, and macro structure. The roles of preheating is very important to avoid significant differentiation between temperature at the base metal, weld metal, and working fluids, also its to avoid craks. Rapid cooling phenomena occurs in in-services welding at welded area which near to the fluided pipe, as a result the area of heat affected zone (HAZ) has a higher hardness value than the base metal and weld metal.